VOLUME ALTERATION IN UNDESCENDED TESTES BEFORE AND AFTER ORCHIOPEXY (The Research of Medical Science Review, 2025)
Background: Undescended testes (cryptorchidism) is a common condition that can lead to fertility issues and increased cancer risk if untreated. While causes are not fully understood, genetic, hormonal, and environmental factors may play a role. Treatment typically involves orchiopexy. However, local studies on testicular volume changes after surgery are scarce, and international data is limited. This study was designed to evaluate the impact of orchiopexy on testicular volume alteration. Objective: To evaluate testicular volume alterations before and after orchiopexy and determination of mean change in testicular volume. Duration: Duration of this study was 6 months, w.e.f September 2024 to Feb 2025.Methodology: This prospective comparative study, conducted at Sandeman Provisional Hospital in Quetta, aimed to assess the impact of orchiopexy on testicular volume in children with cryptorchidism. A total of 31 participants, selected from Civil Hospital Quetta and Bolan Medical Complex, underwent ultrasound imaging before and after surgery, with follow-up between 3 to 6 months. Ultrasonography provided accurate measurements of testicular volume, helping evaluate the efficacy of orchiopexy. Ethical approval was granted, and informed consent was obtained from parents/guardians. Results: The study included 31 participants with a mean age of 7.10 ± 3.29 years. Among them, 45.2% were aged ≤6 years, and 54.8% were 7-12 years old. The undescended testes were located in various positions: above the internal ring (22.6%), at the external ring (64.5%), and prescrotal (12.9%). Paired analysis revealed a significant increase in testicular volume, from 0.387 ± 0.054 ml pre- treatment to 0.567 ± 0.082 ml post-treatment (mean difference: 0.179 ± 0.038 ml, p = 0.000).